Creative capacity of European countries - Alexy, Martin; Káčer, Marek; Rehák, Štefan (Hungarian Geographical Bulletin, 2018)
In the paper4 we study creative capacity of 28 European countries in the period 2005–2014. We construct a creativity index based on the 3Ts concept of talent, technology and tolerance as the key components of the creativity. Our index is measured and calculated with both the cross-section and the time series dimensions, which is an important contribution compared to other studies. We have demonstrated relatively stable rankings of the countries in time, even though the creative capacity measured by our creativity index was gradually growing in time with varying rate of growth for individual countries. We have also shown evidence that the creative capacity is clustered geographically. The creativity index was compared to World happiness index, GDP per capita and Human development index. We have replicated earlier cross-sectional analyses and shown the relatively strong correlation. However, we show that the picture is different for changes within individual countries. Here we demonstrated lack of correlation between creativity and GDP per capita or World happiness index. JEL: O10, O30, O34, C10 4 The paper is an outcome of the research project Competitiveness, economic growth and firm survival (APVV-15-0322) supported by Slovak Research and Development Agency. The research is co-ﬁnanced by the European Union.